2022
DOI: 10.3390/ijerph191911857
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Dislocation Incidence and Risk Factors—Rural vs. Urban Populations of Poland

Abstract: (1) Background: The aim of this study was to analyze the incidence of shoulder dislocation and to estimate non-modifiable risk factors in rural and urban subgroups in Poland. (2) Methods: The study covered the entire Polish population, divided into urban and rural subgroups and observed between 1 January 2014 and 31 December 2014. The study population consisted of Polish patients with a diagnosis of shoulder dislocation (S43.0) in accordance with the International Statistical Classification of Diseases and Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown similar but slightly lower rates of sports-related shoulder dislocations. 10 , 13 , 19 , 21 , 23 Men are more likely to dislocate their shoulders playing sports than women, who are more likely to dislocate their shoulders during nonsports-related activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown similar but slightly lower rates of sports-related shoulder dislocations. 10 , 13 , 19 , 21 , 23 Men are more likely to dislocate their shoulders playing sports than women, who are more likely to dislocate their shoulders during nonsports-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,5,15,22,23 Previous studies have estimated that the incidence of shoulder dislocations is 11.2 to 49.5 per 100,000 person-years in the United States (US) and 15.3 to 56.3 per 100,000 person-years in other countries. 2,6,9,10,16,19,22,23 The data suggest that men are more likely than women to dislocate the shoulder, and dislocations occur in a bimodal age distribution with younger and older groups at most risk. 9,10,16,22,23 The frequency and characteristics of sports-related dislocations in the general population have been studied; nonetheless, its trend over time has yet to be reported.…”
mentioning
confidence: 99%
“…In recent decades, the use of PRP has gained popularity in the field of tissue engineering because of its anti-inflammatory and analgesic properties, as well as its capacity to induce neo-angiogenesis, tissue formation, and remodeling by influencing stem-cell migration, proliferation, and differentiation [ 14 ]. Because of these properties, the clinical use of PRP in the orthopedic field has increased more and more, with it finding an application with encouraging results in the most common orthopedic pathologies, such as muscle lesions, acute and chronic tendinitis, mild osteoarthritis, and osteochondral lesions [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of all these characteristics, PRP has found wide application in clinical practice, useable as local infiltration in many orthopedic diseases, such as as mild osteoarthritis, acute and chronic tendinitis, and plantar fasciitis, as well as in pathologies that are not strictly orthopedic, such as the treatment of chronic wounds and diabetic ulcers, and it has even found application in other fields of medicine, such as plastic surgery and medical esthetics [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder dislocation is a common reason for emergency department (ED) consultation and its incidence rate has been estimated to be approximately 23/100 000 person-years in Europe and North America [1][2][3][4][5]. More specifically, antero-inferior glenohumeral dislocation is the most frequent type (up to 97% of cases) and mostly affects young male adults and older females [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%